Pendampingan Kewirausahaan Bagi Pelaku UMKM Di Desa Gemblegan, Kecamatan Kalikotes, Kabupaten Klaten - Lilia Pasca Riani; Nita Kusumawardani; Sugiharsono Sugiharsono; Mustofa Mustofa; Suyanto Suyanto (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
This Community Service Activity (PPM) aims to provide insight and skills in efforts to increase MSME entrepreneurship in Gemblegan Village, Kalikotes District, Klaten Regency by providing development and improvement of production management and increasing knowledge of online marketing management for MSME players. The problem is resolved in four stages of activity, namely pre-activity, preparation, implementation and evaluation. Preparation was carried out by conducting a preliminary survey to see the real conditions in the field regarding the problems faced by MSMEs in Gemblegan Village, Kalikotes, Klaten. The implementation is carried out by training and mentoring using the lecture method, namely through face-to-face holding in Gemblegan Village by following the prevailing health protocol, followed by discussion and question and answer. Activity evaluation is carried out for each stage through data collection from each activity stage. The methods used in this stage of community service implementation include lectures, question and answer and discussion, training and mentoring. The results of the training showed that the level of understanding of 80% of the participants really understood the material presented by the speakers and. The usefulness of the material shows that 75% of participants strongly agree if the material presented is useful